Modeling the Ruminant Placenta-Pathogen Interactions in Apicomplexan Parasites: Current and Future Perspectives - Pastor-Fernández, Iván; Collantes-Fernández, Esther; Jiménez-Pelayo, Laura; Ortega-Mora, Luis Miguel; Horcajo, Pilar (Frontiers in Veterinary Science, 2021)
Neospora caninum and Toxoplasma gondii are one of the main concerns of the livestock sector as they cause important economic losses in ruminants due to the reproductive failure. It is well-known that the interaction of these parasites with the placenta determines the course of infection, leading to fetal death or parasite transmission to the offspring. However, to advance the development of effective vaccines and treatments, there are still important gaps on knowledge on the placental host-parasite interactions that need to be addressed. Ruminant animal models are still an indispensable tool for providing a global view of the pathogenesis, lesions, and immune responses, but their utilization embraces important economic and ethics restrictions. Alternative in vitro systems based on caruncular and trophoblast cells, the key cellular components of placentomes, have emerged in the last years, but their use can only offer a partial view of the processes triggered after infection as they cannot mimic the complex placental architecture and neglect the activity of resident immune cells. These drawbacks could be solved using placental explants, broadly employed in human medicine, and able to preserve its cellular architecture and function. Despite the availability of such materials is constrained by their short shelf-life, the development of adequate cryopreservation protocols could expand their use for research purposes. Herein, we review and discuss existing (and potential) in vivo, in vitro, and ex vivo ruminant placental models that have proven useful to unravel the pathogenic mechanisms and the host immune responses responsible for fetal death (or protection) caused by neosporosis and toxoplasmosis.